A system dynamics-based decision support model for chemotherapy planning*. Issue 4 (2nd October 2018) - Heshmat, M.; Eltawil, A.
Abstract: This paper introduces a system dynamics model to address the effectiveness of chemotherapy treatment plan. This model includes all the treatment process variables which have been considered in the literature; moreover, we propose new variables such as the impairment caused by both the tumor growth and the adverse effect of chemotherapy doses, and the treatment efficacy which is the response achievable from applying a chemotherapy protocol. Compared to previous works, the results exhibit reasonable decreasing values for the number of cancerous cells and toxicity levels with time. By conducting a sensitivity analysis for the model parameters, the results show that the model is stable and robust for accommodating different values of the parameters. We apply the model on a real chemotherapy protocol for lymphoma, and the proposed model gives a good accommodation of that protocol. A what-if analysis is conducted to the approved chemotherapy protocol via the developed simulation model to check dose cancellation and delay. The results show that the model is sensitive to both dose cancellation and delay, and gives implications about their bad effect on the treatment efficacy.